2021
DOI: 10.3390/ma14185391
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Deposition of Biocompatible and Bioactive Hydroxyapatite-Based Coatings on Titanium

Abstract: Current trends in biomaterials science address the issue of integrating artificial materials as orthopedic or dental implants with biological materials, e.g., patients’ bone tissue. Problems arise due to the simple fact that any surface that promotes biointegration and facilitates osteointegration may also provide a good platform for the rapid growth of bacterial colonies. Infected implant surfaces easily lead to biofilm formation that poses a major healthcare concern since it could have destructive effects an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 146 publications
(254 reference statements)
0
4
0
Order By: Relevance
“…The substitution with carbonate groups occurred between hydroxyl and phosphate groups from HAP, leading to the formation of A-and B-type substituted HAP, respectively, or combined AB-type substitution. 45,54 As represented in Figure 1, the vibrational mode of the O-C-O group can be detected at around 873 cm -1 , while bands in the region 1400-1500 cm -1 can be attributed to the O-C group vibrational mode. 42 Based on the position of carbonate bands in HAP layers grown on the top of HAP/PVA/CS and HAP/PVA/CS/Gent coatings after immersion in SBF at 37 ºC for 7 and 14 days (Table 1), it can be concluded that both AB-and B-type substitution in HAP occurred.…”
Section: Ft-ir Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The substitution with carbonate groups occurred between hydroxyl and phosphate groups from HAP, leading to the formation of A-and B-type substituted HAP, respectively, or combined AB-type substitution. 45,54 As represented in Figure 1, the vibrational mode of the O-C-O group can be detected at around 873 cm -1 , while bands in the region 1400-1500 cm -1 can be attributed to the O-C group vibrational mode. 42 Based on the position of carbonate bands in HAP layers grown on the top of HAP/PVA/CS and HAP/PVA/CS/Gent coatings after immersion in SBF at 37 ºC for 7 and 14 days (Table 1), it can be concluded that both AB-and B-type substitution in HAP occurred.…”
Section: Ft-ir Analysismentioning
confidence: 99%
“…27,29,33,39,40 Due to its numerous advantages (e.g., uniform composition and thickness of the deposited coatings, the possibility of deposition on substrates of complex geometries found in orthopedics, low degree of environmental pollution, and room temperature processing, which is crucial for deposition of bioceramic coatings containing thermolabile antibacterial agents) 41 electrophoretic deposition (EPD) was chosen for the production of biocomposite coatings loaded with Gent. [41][42][43][44][45] Electrophoretic deposition of composite coatings containing chitosan and gentamicin (along with methyl-cellulose, 46 gelatin and bioactive glass, 47 gelatin, silica-gentamicin and bioactive glass, 48 hydroxyapatite 49 , etc.) has been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Electrophoretic deposition of coatings [340][341][342] A relatively simple low-temperature method for forming coatings on an electrically conductive substrate. Virtually indifferent to the shape of the coated surface, it has high productivity and is well adapted to mass production.…”
Section: Chemical Techniquesmentioning
confidence: 99%
“…To increase defense against infections, hydroxyapatite coatings can be doped with Ag and Sr. This modification promotes osteoblast proliferation and especially causes increased levels of alkaline phosphatase biomarkers of osteogenesis [15,16]. Additionally, the addition of strontium in the hydroxyapatite coating improves its adhesion to the substrate [17].…”
Section: Introductionmentioning
confidence: 99%